Genome-Wide Identification of the MdKNOX Gene Family and Characterization of Its Transcriptional Regulation in Malus domestica - Jia, Peng; Zhang, Chenguang; Xing, Libo; Li, Youmei; Shah, Kamran; Zuo, Xiya; Zhang, Dong; An, Na; Han, Mingyu; Ren, Xiaolin (Frontiers in Plant Science, 2020)
Knotted1-like Homeobox (KNOX) proteins play important roles in regulating plant growth, development, and other biological processes. However, little information is available on the KNOX gene family in apple (Malus domestica Borkh.). In this study, 22 KNOX genes were identified in the apple genome. The gene structure, protein characteristics, and promoter region were characterized. The MdKNOX family members were divided into two subfamilies based on their phylogenetic relationships. Quantitative real-time PCR analysis revealed that the majority of MdKNOX genes exhibited strongly preferential expression in buds and were significantly up-regulated during the flower induction period. The transcript levels of MdKNOX genes were responsive to treatments with flowering- and stress-related hormones. The putative upstream regulation factor MdGRF could directly bind to the promoter of MdKNOX15 and MdKNOX19, and inhibit their transcriptional activities, which were confirmed by yeast one-hybrid and dual-luciferase assays. The results provide an important foundation for future analysis of the regulation and functions of the MdKNOX gene family.